Withdrawal of spatial overt attention following intentional forgetting: evidence from eye movements. Issue 4 (21st April 2018) - Lee, Yuh-shiow
ABSTRACT: Eye movements were measured to examine whether item-method directed forgetting involved a spatial overt attention shift. Experiment 1 showed that participants' eyes were moved away from the study word following the forget and ignore cues, but not the remember cue. Experiment 2 revealed that the eyes were moved away from the area that covered by the study word even when the study word disappeared upon the presentation of the memory cue. Both the study word and memory cue were presented auditorily in Experiment 3. In all experiments, the to-be-remembered words were recalled better than both to-be-forgotten and to-be-ignored words. More importantly, mental effort, as indexed by the pupil size, increased following the remember, as compared with the forget and ignore cues. These findings are discussed in terms of controlling spatial overt attention after encoding to withdraw attention from irrelevant information and to allocate cognitive resources to relevant information for long-term retention.